Thermal build-up, decay and retention responses to local therapeutic application of 448 kHz capacitive resistive monopolar radiofrequency: A prospective randomised crossover study in healthy adults. (17th November 2015) - Kumaran, Binoy; Watson, Tim
Abstract: Purpose : Radiofrequency-based electrophysical agents are widely used in therapy-related clinical practice for their thermal effects, mainly relieving pain and inflammation and improving tissue extensibility. The most commonly used and researched are shortwave therapies that operate at 27.12 MHz. Although relatively new, electrophysical agents employing much lower frequencies have also emerged. Capacitive resistive monopolar radiofrequency employing 448 kHz is one such therapy. This laboratory-based study was aimed to investigate the skin thermal responses to 448 kHz radiofrequency-based therapy in healthy adults. Methods : In a two-group randomised crossover study, 15 volunteers attended two modes (capacitive and resistive) of 448 kHz radiofrequency-based therapy (using 'Indiba Activ 902') administered locally to the lower thigh region. Starting at minimum, the intensity was increased incrementally until thermal discomfort was felt. Participants reported three time points: thermal onset, definite thermal sensation, and onset of thermal discomfort. Local skin temperature was measured before, immediately post-treatment and up to 45 min post-treatment. Results : Both capacitive and resistive modes of therapy significantly increased the skin temperature and sustained it over the 45-min follow-up. There was statistically significant difference between the thermal response patterns produced by the two modes. Peak post-treatment temperatures attained were not significantly different between the two; however, the retention rate at follow-up was significantly higher for the resistive mode. Conclusions : This study confirms that radiofrequency-based therapy at 448 kHz can significantly increase and sustain skin temperature. The study also provides useful baseline data for further research in the low frequency ranges of radiofrequency-based therapy that remain largely unexplored.